2015
DOI: 10.1111/ijfs.12914
|View full text |Cite
|
Sign up to set email alerts
|

Selective fractionation of cholesterol from whole milk powder: optimisation of supercritical process conditions

Abstract: Supercritical fluid extraction (SCFE) of cholesterol from whole milk powder (WMP) was investigated in this study. The combined effects of temperature (40-80°C) and pressure (150-250 bar) on the efficacy of cholesterol extraction (mg 100 g À1 ), modifications in the fat content (FC) (%) and solubility index (SI) (%) of WMP were studied and optimised by the application of response surface methodology (RSM). Variations in the free fatty acids (FFAs) (mg oleic acid per 100 g of milk fat) and lightness value (L*) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Cholesterol solubility increased with the increase in pressure at constant temperature owing to the rise in solvent density. Chitra et al observed a significant increase in the extraction of cholesterol from WMP as the extraction pressure increased from 15 to 20 MPa. However, above 20 MPa, with increasing pressure at constant temperature the selectivity of cholesterol over the amount of the extracted milk fat was reduced; the extraction temperature ranged from 40 to 80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol solubility increased with the increase in pressure at constant temperature owing to the rise in solvent density. Chitra et al observed a significant increase in the extraction of cholesterol from WMP as the extraction pressure increased from 15 to 20 MPa. However, above 20 MPa, with increasing pressure at constant temperature the selectivity of cholesterol over the amount of the extracted milk fat was reduced; the extraction temperature ranged from 40 to 80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…CO 2 gas was released from the CO 2 tank and its temperature was lowered to −4 °C by passing it through a chiller before entering the pressure vessel. The flow rate of expanded CO 2 from the tank was kept constant at 6 L min −1 as it was observed to be the most favorable condition for the required extraction . The low flow rate allows high residence time of the solvent in the extraction vessel .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, supercritical fluid extraction (SFE) has been gaining interest in recent years, because in addition to being considered a "green" extraction method, it has other advantages (Poliakoff and Licence, 2015) such as fractionation selectivity (Chitra et al, 2015), higher yields of bioactive compounds as compared to those of conventional methods (Farías-Campomanes et al, 2013), and the fact that it can be performed at low temperatures, avoiding the degradation of thermosensitive substances. A supercritical fluid is any pure substance at a pressure and temperature above its critical point where distinct liquid and gas phases do not exist (Knez et al, 2014) (Figure 7).…”
Section: Extraction Of Biomolecules Of M Charantia With Supercriticamentioning
confidence: 99%
“…First, extraction is performed by maintaining the temperature and pressure of the fluid above the critical point. Second, the separation step changes the phase of the supercritical fluid to the gas phase by depressurization to release the extract with no chemical or toxic residues (Lang and Wai 2001;Cheah et al 2006;Herrero et al 2006;Fornari et al 2012;Chitra et al 2015;Martin et al 2015). The parameters that affect the extraction efficiency include the characteristics of the sample preparation-such as the sample size, homogeneity of the sample, and water/moisture content-and extraction parameters-such as the pressure, temperature, flow rate, and extraction time.…”
mentioning
confidence: 99%